Industrial solid waste unfired haydite, preparation method and application thereof

CN122897618APending Publication Date: 2026-10-13TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611382206.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

解决循环流化床粉煤灰活性不足,导致免烧陶粒反应产物少及强度低的问题;以及循环流化床粉煤灰CaO含量高,导致陶粒后期体积膨胀强度降低的难题

Benefits of technology

1、本发明避免了循环流化床粉煤灰活性激发不足,导致免烧陶粒内部生成产物较少、强度低等问题。在球磨过程中电石渣中Ca(OH)2以及脱硫石膏中CaSO4协同球磨破坏粉煤灰中Si-O键和Al-O键,可促进硅铝酸盐玻璃网格解聚,释放出活性SiO2和活性Al2O3,显著激发粉煤灰的火山灰活性。此外,采用饱和石灰水养护的方式,使得循环流化床粉煤灰活性进一步激发的同时与体系中Ca2+发生火山灰反应,生成具有胶凝性的C-S-H(水化硅酸钙)与C-A-H(水化铝酸钙)以及钙矾石(AFt)等,同时结合恒温恒湿养护以及自然养护,大幅加深水化程度,提升陶粒的强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897618A_ABST
    Figure CN122897618A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of ceramic granule preparation, and particularly relates to an industrial solid waste unfired ceramic granule and a preparation method and application thereof. The industrial solid waste unfired ceramic granule is obtained by granulation forming and curing in a composite curing mode; the raw materials include circulating fluidized bed fly ash, cement, carbide slag and desulfurization gypsum. The application solves the key problems of low activity of the circulating fluidized bed fly ash, low hydration product and low strength of the unfired ceramic granule, and solves the problem of low strength of the ceramic granule caused by high CaO content of the circulating fluidized bed fly ash. In addition, the raw materials are mainly industrial solid wastes, and the preparation process does not need calcination, so that the obtained unfired ceramic granule has low cost and high strength, and can realize resource utilization of the industrial solid wastes, and is suitable for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ceramsite preparation technology, specifically relating to an industrial solid waste non-fired ceramsite, its preparation method, and its application. Background Technology

[0002] Expanded clay aggregate (ECA) has advantages such as low density, light weight, good thermal insulation, and high fire resistance and earthquake resistance, and has been rapidly developed and applied worldwide in recent years. Traditional ECA production mainly uses natural minerals such as shale and clay as raw materials. Although the technology is mature and widely used, it has high energy consumption, large raw material consumption, and limited natural mineral resources, making sustainable development difficult.

[0003] Circulating fluidized bed fly ash, carbide slag, and desulfurization gypsum are typical industrial solid wastes, with huge emissions and stockpiles. The main components of circulating fluidized bed fly ash are Al₂O₃ and SiO₂, the main component of carbide slag is Ca(OH)₂, and the main component of desulfurization gypsum is CaSO₄·2H₂O. If these industrial solid wastes can be used to prepare non-fired ceramsite, it can not only significantly reduce production energy consumption and costs, but also provide a new method for solid waste disposal and resource utilization, possessing significant economic value and environmental benefits.

[0004] Fly ash-based non-fired ceramsite refers to ceramsite made primarily from fly ash. The process involves granulation with added additives and binders, without high-temperature calcination, followed by natural curing, steam curing, or autoclaving. Its strength development mechanism is based on chemical activation. During curing, the active oxides (SiO2 and Al2O3) in the fly ash react with Ca in the system under the action of an alkaline activator. 2+ The reaction produces hydraulic cementitious products such as hydrated calcium silicate (CSH) and hydrated calcium aluminate (CAH), which improve the mechanical properties of the ceramsite. Compared with traditional sintered ceramsite, this non-sintering process has significant advantages such as high raw material utilization, simple process, no need for large-scale high-temperature equipment, and green environmental protection, and has broad development prospects.

[0005] Due to the differences in fuel types and combustion methods between circulating fluidized bed boilers and pulverized coal boilers, the physicochemical properties of circulating fluidized bed fly ash differ significantly from those of conventional fly ash (pulverized coal boiler fly ash). Conventional fly ash particles are mostly regularly spherical with smooth surfaces, while circulating fluidized bed fly ash particles are mostly irregularly shaped with porous and uneven surfaces. The chemical composition of circulating fluidized bed fly ash is similar to that of conventional fly ash, but its CaO and SO3 content is significantly higher. Its pozzolanic activity is superior to that of conventional fly ash. However, due to its higher CaO content, this to some extent increases the Ca content in the system. 2+The content of calcite is important, but if the degree of hydration is insufficient in the early stages, the continuous hydration reaction in the later stages can lead to excessive growth of ettringite inside the ceramsite, causing problems such as expansion, reduced strength, and even cracking of the ceramsite, seriously affecting its performance. Therefore, the activation degree of volcanic ash activity and the degree of hydration in circulating fluidized bed fly ash are more critical.

[0006] Existing technologies for non-fired ceramsite of fly ash mainly target traditional fly ash, using NaOH, Ca(OH)2, or gypsum as activators to enhance fly ash activity. This approach is costly and yields insufficient activation. This invention proposes a method of co-milling industrial solid waste carbide slag and desulfurization gypsum, followed by saturated lime water soaking and curing, to activate fly ash activity, promote early hydration reactions, and enhance the internal Ca content of the fly ash. 2+ This invention offers low consumption, low cost, and good activation effect. Currently, methods such as natural curing, steam curing, or autoclaving are commonly used to accelerate the hydration process of fly ash, but these methods often result in insufficient hydration. This invention proposes a saturated lime water soaking curing method, which allows the hydration reaction to occur simultaneously with the activation of the non-fired ceramsite. Combined with constant temperature and humidity curing and natural curing, this significantly deepens the hydration level, thereby improving the strength of the non-fired ceramsite. Furthermore, this invention proposes a pure CO2 mineralization curing method, which reduces the Ca content in the system... 2+ It reacts with CO2 to form calcium carbonate, consuming Ca. 2+ At the same time, calcium carbonate can fill the micropores in the ceramsite in situ, further improving the strength of the ceramsite, reducing the excessive growth of ettringite in the later stage, and alleviating the problem of reduced strength or even cracking of the ceramsite in the later stage. Summary of the Invention

[0007] The purpose of this invention is to provide an industrial solid waste non-fired ceramsite, its preparation method, and its application. It solves the problems of insufficient activity of circulating fluidized bed fly ash, leading to low reaction products and low strength in the non-fired ceramsite; and the difficulty of high CaO content in circulating fluidized bed fly ash causing reduced strength due to later volume expansion of the ceramsite. The prepared non-fired ceramsite has the characteristics of low cost, high strength, and simple preparation method.

[0008] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing non-fired ceramsite from industrial solid waste, comprising the following steps: The raw materials are mixed and then granulated to obtain granules; the raw materials include circulating fluidized bed fly ash, carbide slag, desulfurization gypsum and cement; The particles are cured to obtain the industrial solid waste non-fired ceramsite. The maintenance includes first-level maintenance, second-level maintenance, third-level maintenance and fourth-level maintenance performed in sequence; The first-stage curing method is soaking in a saturated lime water solution; The second-level curing method is mineralization curing in a pure carbon dioxide atmosphere; The third level of maintenance is constant temperature and humidity maintenance; The fourth level of maintenance is natural maintenance in an indoor environment.

[0009] Preferably, the raw materials, by mass percentage, include: 70%–85% circulating fluidized bed fly ash, 5%–10% carbide slag, 5%–10% desulfurized gypsum, and 5%–10% cement.

[0010] Preferably, the mass percentage of Ca(OH)2 in the carbide slag is ≥90%; the mass percentage of CaSO4·2H2O in the desulfurized gypsum is ≥90%; and the cement is ordinary Portland cement.

[0011] Preferably, the mixing includes sequential stirring and ball milling; the ball milling time is 30-60 minutes. The particle size of the material obtained after ball milling is 50~150μm.

[0012] Preferably, the granulation process further includes spraying water onto the surface of the material, wherein the water-to-solid ratio is 0.2 to 0.5.

[0013] Preferably, the temperature of the saturated lime aqueous solution is 20±3℃, and the soaking and curing time is 6~12h.

[0014] Preferably, the mineralization curing temperature is 50~150℃, the pressure is 0.5~1.5MPa, and the time is 6~12h.

[0015] Preferably, the temperature for constant temperature and humidity curing is 20±3℃, the relative humidity is 90±2%, and the time is 12~24h; The natural maintenance period is 7 to 28 days.

[0016] The present invention also provides industrial solid waste non-fired ceramsite prepared by the preparation method described in the above technical solution.

[0017] This invention also provides the application of the above-described industrial solid waste non-fired ceramsite in green building materials or road engineering.

[0018] Compared with the prior art, the positive and beneficial effects achieved by this invention are as follows: 1. This invention avoids the problems of insufficient activation of circulating fluidized bed fly ash, leading to fewer internal products and lower strength in the non-fired ceramsite. During ball milling, Ca(OH)2 in the carbide slag and CaSO4 in the desulfurized gypsum synergistically break down Si-O and Al-O bonds in the fly ash, promoting the deagglomeration of the aluminosilicate glass mesh and releasing active SiO2 and active Al2O3, significantly activating the pozzolanic activity of the fly ash. Furthermore, the use of saturated lime water curing further activates the circulating fluidized bed fly ash while simultaneously reacting with Ca in the system. 2+ A volcanic ash reaction occurs, generating cementitious CSH (hydrated calcium silicate), CAH (hydrated calcium aluminate), and ettringite (AFt), etc. At the same time, combined with constant temperature and humidity curing and natural curing, the degree of hydration is greatly deepened, and the strength of the ceramsite is improved.

[0019] 2. This invention avoids the problem of high CaO content in circulating fluidized bed fly ash, which leads to volume expansion, reduced strength, and even cracking of the unfired ceramsite during later hydration. This invention proposes a pure CO2 mineralization curing method, which reduces the CaO content in the system. 2+ It is consumed in large quantities during the early curing process. It reacts with CO2 to generate stable calcium carbonate, which fills the micropores of the ceramsite, improves the strength of the ceramsite, and greatly reduces the later hydration reaction.

[0020] 3. The preparation process of this invention is simple, with low cement consumption, and it eliminates the need for secondary pelletizing, saving preparation time. Furthermore, this invention utilizes industrial solid waste, including circulating fluidized bed fly ash, carbide slag, and desulfurized gypsum, to prepare non-fired ceramsite. The circulating fluidized bed fly ash accounts for over 70%, and the industrial solid waste accounts for over 90%, resulting in low preparation costs and achieving resource utilization of industrial solid waste. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of the preparation process of non-fired ceramsite from industrial solid waste. Detailed Implementation

[0022] This invention provides a method for preparing non-fired ceramsite from industrial solid waste, comprising the following steps: The raw materials are mixed and then granulated to obtain granules; the raw materials include circulating fluidized bed fly ash, carbide slag, desulfurization gypsum and cement; The particles are cured to obtain the industrial solid waste non-fired ceramsite. The maintenance includes first-level maintenance, second-level maintenance, third-level maintenance and fourth-level maintenance performed in sequence; The first-stage curing method is soaking in a saturated lime water solution; The second-level curing method is mineralization curing in a pure carbon dioxide atmosphere; The third level of maintenance is constant temperature and humidity maintenance; The fourth level of maintenance is natural maintenance in an indoor environment.

[0023] This invention involves mixing raw materials and then granulating them to obtain granules; the raw materials include circulating fluidized bed fly ash, carbide slag, desulfurized gypsum, and cement.

[0024] In this invention, the raw materials preferably include, by mass percentage: 70%–85% circulating fluidized bed fly ash, 5%–10% carbide slag, 5%–10% desulfurized gypsum, and 5%–10% cement. Specifically, the content of circulating fluidized bed fly ash can be 70%, 75%, 80%, or 85%; the content of carbide slag can be 5%, 6%, 7%, 8%, 9%, or 10%; the content of desulfurized gypsum can be 5%, 6%, 7%, 8%, 9%, or 10%; and the content of cement can be 5%, 6%, 7%, 8%, 9%, or 10%.

[0025] In this invention, the mass percentage of Ca(OH)2 in the carbide slag is preferably ≥90%; the mass percentage of CaSO4·2H2O in the desulfurized gypsum is preferably ≥90%; and the cement preferably includes ordinary Portland cement, and the type of ordinary Portland cement is preferably P·O 42.5.

[0026] In this invention, the mixing preferably includes stirring and ball milling performed sequentially; the ball milling time is 30 to 60 minutes, specifically 30 minutes, 40 minutes, 50 minutes, or 60 minutes; the particle size of the material obtained after ball milling is preferably 50 to 150 μm.

[0027] In this invention, the granulation process preferably includes spraying water onto the surface of the material, wherein the water-to-solid ratio is preferably 0.2 to 0.5, specifically 0.2, 0.3, 0.4, or 0.5.

[0028] After obtaining the particles, the present invention cures the particles to obtain the industrial solid waste non-fired ceramsite.

[0029] In this invention, the maintenance includes a first-level maintenance, a second-level maintenance, a third-level maintenance, and a fourth-level maintenance performed sequentially.

[0030] In this invention, the first-stage curing method is to soak in a saturated lime water solution; the temperature of the saturated lime water solution is preferably 20±3℃; the soaking time is preferably 6~12h, specifically 6h, 7h, 8h, 9h, 10h, 11h, or 12h.

[0031] In this invention, the second-stage curing method is mineralization curing in a pure carbon dioxide atmosphere; the preferred temperature for mineralization curing is 50~150℃, specifically 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, 110℃, 120℃, 130℃, 140℃, or 150℃; the preferred pressure is 0.5~1.5MPa, specifically 0.5MPa, 0.6MPa, 0.7MPa, 0.8MPa, 0.9MPa, 1.0MPa, 1.1MPa, 1.2MPa, 1.3MPa, 1.4MPa, or 1.5MPa; and the preferred time is 6~12h, specifically 6h, 7h, 8h, 9h, 10h, 11h, or 12h.

[0032] In this invention, the third-level curing method is constant temperature and humidity curing; the preferred temperature for constant temperature and humidity curing is 20±3℃; the preferred relative humidity is 90±2%; and the preferred time is 12~24h, specifically 12h, 14h, 16h, 18h, 20h, 22h, and 24h.

[0033] In this invention, the fourth level of maintenance is natural maintenance in an indoor environment; the natural maintenance time is preferably 7 to 28 days, specifically 7 days, 14 days, or 28 days.

[0034] In this invention, the main component of carbide slag is Ca(OH)2. Free CaO in the circulating fluidized bed fly ash and tricalcium silicate (C3S) and dicalcium silicate (C2S) in the cement hydrate to form Ca(OH)2. Simultaneously, tricalcium silicate (C3S) and dicalcium silicate (C2S) in the cement continuously hydrate to form hydrated calcium silicate (CSH) gel, gradually filling the internal pores of the particles and improving the strength of the non-fired ceramsite. Under the combined activating effect of Ca(OH)2 and CaSO4 in the desulfurized gypsum, SiO2 and Al2O3 in the circulating fluidized bed fly ash are activated and react with Ca(OH)2 to form CSH (hydrated calcium silicate) and CAH (hydrated calcium aluminate), which have cementing properties, thus improving the strength of the ceramsite to a certain extent. At the same time, CaSO4·2H2O in the desulfurized gypsum can react with Ca(OH)2 and Al2O3 or calcium aluminate to form ettringite (AFt), further enhancing the strength of the ceramsite. Furthermore, under a pure CO2 atmosphere, Ca(OH)2 reacts with CO2 to undergo a carbonation reaction to generate CaCO3. Simultaneously, the CSH gel generated during hydration can also react with CO2 to undergo a carbonation reaction to generate CaCO3, thus improving the compressive strength of the ceramsite. After curing with saturated lime water, mineralization curing, and constant temperature and humidity curing, the unfired ceramsite is placed in an indoor environment for natural curing, continuing to undergo hydration and carbonation reactions with H2O and CO2 in the air, further enhancing the strength of the oxygen-carrying particles. The main chemical equations are as follows: .

[0035] The present invention also provides industrial solid waste non-fired ceramsite prepared by the preparation method described in the above technical solution.

[0036] In this invention, the compressive strength of the industrial solid waste non-fired ceramsite is 8~12MPa.

[0037] This invention also provides the application of the above-described industrial solid waste non-fired ceramsite in green building materials or road engineering.

[0038] Unless otherwise specified, the materials and equipment used in this invention are all commercially available products in the field.

[0039] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0040] Example 1 (1) Based on mass percentage, 70% circulating fluidized bed fly ash, 10% carbide slag (with Ca(OH)2 content ≥90%), 10% desulfurized gypsum (CaSO4·2H2O content ≥90%) and 10% cement (P·O42.5 ordinary Portland cement) are mixed in a mixer to obtain a uniformly mixed dry powder material; the dry powder material is put into a ball mill for ball milling, and after ball milling for 30 minutes, a material with a particle size of 50-100μm is obtained; the ball-milled material is put into a disc granulator for granulation, and water is sprayed evenly on the surface of the material at a water-to-solid ratio of 0.3 during the granulation process to obtain granules; (2) Soak the granules in a saturated lime water solution at a temperature of 20±3℃ for 6 hours; then place them in a pure CO2 atmosphere for mineralization curing at a pressure of 1MPa, a temperature of 80℃, and a curing time of 6 hours; then place them in a constant temperature and humidity curing room at a temperature of 20±3℃ and a relative humidity of 90±2% for 12 hours; finally, place them in an indoor environment for natural curing for 28 days to obtain non-fired ceramsite.

[0041] Example 2 Non-fired ceramsite was prepared according to the method described in Example 1; The ball milling time is 40 minutes.

[0042] Example 3 Non-fired ceramsite was prepared according to the method described in Example 1; The ball milling time is 60 minutes.

[0043] The compressive strength of the non-fired ceramsite prepared in Examples 1 to 3 was tested. The test method was as follows: 20 pieces of the prepared non-fired ceramsite were taken and the compressive strength of the non-fired ceramsite was tested using a universal testing machine. The arithmetic mean value was taken as the compressive strength of the non-fired ceramsite. The results are shown in Table 1. Table 1. Compressive strength of the non-fired ceramsite prepared in Examples 1-3

[0044] As can be seen from the test results of Examples 1 to 3 in Table 1, the compressive strength of the non-fired ceramsite increases with the increase of ball milling time.

[0045] Example 4 Non-fired ceramsite was prepared according to the method described in Example 1; The curing time for soaking in saturated lime water solution is 8 hours.

[0046] Example 5 Non-fired ceramsite was prepared according to the method described in Example 1; The curing time for soaking in saturated lime water solution is 12 hours.

[0047] The compressive strength of the non-fired ceramsite prepared in Examples 4 and 5 was tested using the methods described above; the results are shown in Table 2. Table 2. Compressive strength of the non-fired ceramsite prepared in Examples 1 and 4-5

[0048] As can be seen from the test results of Examples 1 and 4-5 in Table 2, the compressive strength of the non-fired ceramsite increases with the increase of the soaking and curing time in saturated lime water solution.

[0049] Example 6 Non-fired ceramsite was prepared according to the method described in Example 1; The mineralization curing time is 8 hours.

[0050] Example 7 Non-fired ceramsite was prepared according to the method described in Example 1; The mineralization curing time is 12 hours.

[0051] The compressive strength of the non-fired ceramsite prepared in Examples 6 and 7 was tested using the methods described above; the results are shown in Table 3. Table 3. Compressive strength of the non-fired ceramsite prepared in Examples 1 and 6-7

[0052] As can be seen from the test results of Examples 1 and 6-7 in Table 3, the compressive strength of the non-fired ceramsite increases with the increase of mineralization curing time.

[0053] Example 8 Non-fired ceramsite was prepared according to the method described in Example 1; Among them, the constant temperature and humidity curing room is used for curing for 18 hours.

[0054] Example 9 Non-fired ceramsite was prepared according to the method described in Example 1; Among them, the constant temperature and humidity curing room is used for 24-hour curing.

[0055] The compressive strength of the non-fired ceramsite prepared in Examples 8-9 was tested, and the test methods were as described above. The results are shown in Table 4. Table 4. Compressive strength of the non-fired ceramsite prepared in Examples 1 and 8-9

[0056] As can be seen from the test results of Examples 1 and 8-9 in Table 4, the compressive strength of the non-fired ceramsite increases with the increase of the curing time in the constant temperature and humidity curing room.

[0057] Example 10 Non-fired ceramsite was prepared according to the method described in Example 1; The natural maintenance period is 7 days.

[0058] Example 11 Non-fired ceramsite was prepared according to the method described in Example 1; The natural maintenance period is 14 days.

[0059] The compressive strength of the non-fired ceramsite prepared in Examples 10 and 11 was tested using the same methods as above, and the results are shown in Table 5. Table 5. Compressive strength of the non-fired ceramsite prepared in Examples 1 and 10-11

[0060] As can be seen from the test results of Examples 1 and 10-11 in Table 5, the compressive strength of the non-fired ceramsite increases with the increase of natural curing time.

[0061] Comparative Example 1 Non-fired ceramsite was prepared according to the method described in Example 1; The raw material composition, by mass percentage, consists of 70% circulating fluidized bed fly ash, 20% carbide slag, and 10% cement, excluding desulfurized gypsum.

[0062] Comparative Example 2 Non-fired ceramsite was prepared according to the method described in Example 1; The raw material composition, by mass percentage, consists of 70% circulating fluidized bed fly ash, 20% desulfurized gypsum, and 10% cement, excluding carbide slag.

[0063] The compressive strength of the non-fired ceramsite prepared in Comparative Examples 1 and 2 was tested according to the above test method, and the results are shown in Table 6. Table 6. Compressive strength of the non-fired ceramsite prepared in Example 1 and Comparative Examples 1-2

[0064] As shown in Table 6, the test results of Example 1 and Comparative Examples 1-2 indicate that adding desulfurized gypsum or carbide slag can activate the activity of circulating fluidized bed fly ash, accelerate the hydration reaction, and improve the compressive strength of the non-fired ceramsite. Carbide slag exhibits a stronger activating ability. Furthermore, desulfurized gypsum and carbide slag can synergistically activate the activity of circulating fluidized bed fly ash, further enhancing the compressive strength of the non-fired ceramsite.

[0065] Comparative Example 3 Non-fired ceramsite was prepared according to the method described in Example 1; Ball milling was not performed.

[0066] The compressive strength of the non-fired ceramsite prepared in Comparative Example 3 was tested using the same method as above, and the results are shown in Table 7. Table 7 Compressive strength of the non-fired ceramsite prepared in Example 1 and Comparative Example 3

[0067] As can be seen from the test results of Example 1 and Comparative Example 3 in Table 7, ball milling can break the Si-O and Al-O bonds in fly ash, promote the deagglomeration of aluminosilicate glass mesh, release active SiO2 and active Al2O3, stimulate the pozzolanic activity of fly ash, and thus significantly enhance the compressive strength of non-fired ceramsite.

[0068] Comparative Example 4 Non-fired ceramsite was prepared according to the method described in Example 1; None of them were soaked and cured in saturated lime water solution; The compressive strength of the non-fired ceramsite prepared in Comparative Example 4 was tested using the same method as above, and the results are shown in Table 8. Table 8. Compressive strength of the non-fired ceramsite prepared in Example 1 and Comparative Example 4

[0069] As shown in Table 8, the test results of Example 1 and Comparative Example 4 indicate that soaking and curing with saturated lime water can break the Si-O and Al-O bonds in fly ash, activate the pozzolanic activity of fly ash, and simultaneously provide the Ca required for the hydration reaction. 2 + This significantly enhances the compressive strength of the non-fired ceramsite.

[0070] Comparative Example 5 Non-fired ceramsite was prepared according to the method described in Example 1; Mineralization maintenance was not carried out in these areas; The compressive strength of the non-fired ceramsite prepared in Example 1 and Comparative Example 5 was tested. In order to analyze the effect of later expansion on the compressive strength of the non-fired ceramsite, the compressive strength of the non-fired ceramsite prepared in Example 1 and Comparative Example 5 was tested after being placed in an indoor environment for 100 days. The test methods are as above, and the results are shown in Table 9. Table 9 Compressive strength of the non-fired ceramsite prepared in Example 1 and Comparative Example 5

[0071] As shown in Table 9, the test results of Example 1 and Comparative Example 5 indicate that the compressive strength of the unfired ceramsite that had not undergone mineralization curing decreased after being left to stand naturally for 100 days. This was mainly due to the excessive growth of ettringite in the later stages, leading to expansion or localized cracking of the ceramsite. Mineralization curing can reduce the Ca content in the system. 2+ It is consumed in large quantities during the early curing process. It reacts with CO2 to generate stable calcium carbonate, which fills the micropores of the ceramsite and improves the compressive strength of the non-fired ceramsite. At the same time, it inhibits the excessive growth of ettringite in the later stage, effectively solving the problem of reduced compressive strength of non-fired ceramsite in the later stage.

[0072] Comparative Example 6 Non-fired ceramsite was prepared according to the method described in Example 1; None of them were cured in a constant temperature and humidity curing room; The compressive strength of the non-fired ceramsite prepared in Comparative Example 6 was tested using the same method as above, and the results are shown in Table 10. Table 10 Compressive strength of the non-fired ceramsite prepared in Example 1 and Comparative Example 6

[0073] As can be seen from the test results of Example 1 and Comparative Example 6 in Table 10, curing in a constant temperature and humidity curing room can accelerate the hydration reaction and improve the compressive strength of the non-fired ceramsite.

[0074] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing non-fired ceramsite from industrial solid waste, characterized in that, Includes the following steps: The raw materials are mixed and then granulated to obtain granules; the raw materials include circulating fluidized bed fly ash, carbide slag, desulfurization gypsum and cement; The particles are cured to obtain the industrial solid waste non-fired ceramsite. The maintenance includes first-level maintenance, second-level maintenance, third-level maintenance and fourth-level maintenance performed in sequence; The first-stage curing method is soaking in a saturated lime water solution; The second-level curing method is mineralization curing in a pure carbon dioxide atmosphere; The third level of maintenance is constant temperature and humidity maintenance; The fourth level of maintenance is natural maintenance in an indoor environment.

2. The preparation method according to claim 1, characterized in that, The raw materials, by mass percentage, include: 70%–85% circulating fluidized bed fly ash, 5%–10% carbide slag, 5%–10% desulfurized gypsum, and 5%–10% cement.

3. The preparation method according to claim 2, characterized in that, The carbide slag contains ≥90% Ca(OH)2 by mass; the desulfurized gypsum contains ≥90% CaSO4·2H2O by mass; and the cement is ordinary Portland cement.

4. The preparation method according to claim 1, characterized in that, The mixing process includes sequential stirring and ball milling; the ball milling time is 30-60 minutes. The particle size of the material obtained after ball milling is 50~150μm.

5. The preparation method according to claim 1, characterized in that, The granulation process also includes spraying water onto the surface of the material, wherein the water-to-solid ratio is 0.2 to 0.

5.

6. The preparation method according to claim 1, characterized in that, The temperature of the saturated lime aqueous solution is 20±3℃, and the soaking and curing time is 6~12h.

7. The preparation method according to claim 1, characterized in that, The mineralization curing temperature is 50~150℃, the pressure is 0.5~1.5MPa, and the time is 6~12h.

8. The preparation method according to claim 1, characterized in that, The constant temperature and humidity curing temperature is 20±3℃, the relative humidity is 90±2%, and the time is 12~24h; The natural maintenance period is 7 to 28 days.

9. The industrial solid waste non-fired ceramsite prepared by the preparation method according to any one of claims 1 to 8.

10. The application of the industrial solid waste non-fired ceramsite as described in claim 9 in green building materials or road engineering.